Fault detection in power transmission line using neuro-fuzzy - 395612 Elly Yuza Mahmud (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2006